Stress heterogeneity and complexity: implications for mining - Beck, D.; Windsor, Christopher; Reusch, F.; Player, John (American Rock Mechanics Association, 2012)
Stress fields in a disturbed discontinuum such as the Earth’s crust should be complex, and yet most mines make do with a handful of measurements not sufficient in coverage or number to capture the complexity of this fundamental input to mine design. Observations confirm that at a mine scale and smaller, the variability in stress gradients is sufficient to affect excavation performance. At a number of example mines, an effort was made to explain and match the measured variability by numerically simulating aspects of the geo-mechanical history. By accounting for the structural geometry, topography or a simple interpretation of the geological history, these simple numerical models help explain the variability between measurements and confirm measured heterogeneity of the stress field at a scale that is relevant to mine performance.